2018
DOI: 10.1038/s41598-018-30298-9
|View full text |Cite
|
Sign up to set email alerts
|

Phyllostachys edulis forest reduces atmospheric PM2.5 and PAHs on hazy days at suburban area

Abstract: This study is aim to illustrate Phyllostachys edulis’ role in affecting air quality under hazy day and solar day. P. edulis is a crucial plants growing well at suburban area at China Southern. In this manuscript, on 2 weather conditions (hazy day; solar day), changes in atmospheric particulate matter (PM), polycyclic aromatic hydrocarbons (PAHs), associated volatile organic compounds (VOCs), and PAHs in leaves and soils were measured, with PM-detection equipment and the GC-MC method, in a typical bamboo forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 64 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Here, P. nigra had the lowest PM density of the three analysed species but still was effective in collecting airborne particles, especially PM1, despite being in the inner side of the green barrier. Some studies have shown that other bamboo plants capture PM2.5 and PM10, such as Phyllosthachys bissetti (Morina et al, 2013), or can lower the atmospheric concentrations of these contaminants, such as a Phyllostachys edulis forest in China (Bi et al, 2018). The P. nigra specimens in our study also helped shape the green barrier and make it denser, which is highly important for the deflection effect of the barrier on air pollution (Tomson et al, 2021).…”
Section: Species Variation In Pm Capturementioning
confidence: 55%
“…Here, P. nigra had the lowest PM density of the three analysed species but still was effective in collecting airborne particles, especially PM1, despite being in the inner side of the green barrier. Some studies have shown that other bamboo plants capture PM2.5 and PM10, such as Phyllosthachys bissetti (Morina et al, 2013), or can lower the atmospheric concentrations of these contaminants, such as a Phyllostachys edulis forest in China (Bi et al, 2018). The P. nigra specimens in our study also helped shape the green barrier and make it denser, which is highly important for the deflection effect of the barrier on air pollution (Tomson et al, 2021).…”
Section: Species Variation In Pm Capturementioning
confidence: 55%
“…In Shanghai, China, the annual PM 2.5 reduction can reach 442.4 t per year [ 151 ]. There may be a connection between trees’ ability to purify the air and the following factors: an increase in vegetation cover lowers the sources of PM 2.5 ; various tree organs can absorb PM; a decrease in wind speed may cause PM fallout; and a change in wind direction may stop PM 2.5 from being transported into specific areas [ 152 ]. The capacity of trees to filter out PM 2.5 is influenced by many variables, including meteorological conditions, tree biological features, and atmospheric PM 2.5 and PM 10 concentrations [ 152 ].…”
Section: Green Urban Architecture and Their Impactmentioning
confidence: 99%
“…The possibility of using trees to reduce the amount of air particles has been the subject of research. Recent studies have shown that avenue trees, particularly in urban and suburban environments, may dramatically lower PM 2.5, and absorb gaseous air pollutants [ 152 , 169 ]. Jayasooriya et al [ 133 ] reported that combining various GI, such as GWs and GRs, did not significantly enhance the air quality.…”
Section: Avenue Trees: Potentials and Possibilitiesmentioning
confidence: 99%
“…Hazy weather is a normal event in China [1] that can severely increase the occurrence of air pollution [2]. It is characterized by scattering of particles which constitute the main factor for visibility degradation [3, 4].…”
Section: Introductionmentioning
confidence: 99%